2021
DOI: 10.1002/osp4.569
|View full text |Cite
|
Sign up to set email alerts
|

Inositol supplementation and body mass index: A systematic review and meta‐analysis of randomized clinical trials

Abstract: Background: Inositol is a sugar-alcohol and recognized as a key component of cell membrane phospholipids. It has crucial role in the cell signaling pathways and contribute to improving glycemic responses. Although some earlier studies have revealed the effect of inositol mediating glucose uptake by improving insulin sensitivity, the benefit of inositol supplementation in patients with overweight and obesity is not completely understood. This study aimed to assess the impact of inositol supplementation on body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…This finding is consistent with the results of previous studies (Fruzzetti et al, 2017;Pintaudi et al, 2016). For example, showed that inositol supplementation significantly reduced BMI (Zarezadeh et al, 2022). In diabetic rats, supplementation with inositol derivatives, especially inositol hexaphosphate (IP6), resulted in weight reduction through increasing serum leptin, which in turn regulated food intake (Foster et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with the results of previous studies (Fruzzetti et al, 2017;Pintaudi et al, 2016). For example, showed that inositol supplementation significantly reduced BMI (Zarezadeh et al, 2022). In diabetic rats, supplementation with inositol derivatives, especially inositol hexaphosphate (IP6), resulted in weight reduction through increasing serum leptin, which in turn regulated food intake (Foster et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported the effectiveness of DCI and MI in improving obesity-related complications in patients with PCOS and metabolic syndrome (Giordano et al, 2011;Unfer et al, 2016;Zheng et al, 2015) diets, dietary supplements, and exercise. The beneficial effect of inositol on obesity and related disorders may be explained by its involvement in insulin signaling and improving insulin sensitivity (Zarezadeh et al, 2022). However, the short duration of the trial and the difference in the type of disease in the studied population are also involved in inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, metformin/myo-inositol combination therapy, but not metformin alone, tended to reduce BMI. This observation is in line with the results of a recent meta-analysis of 15 controlled clinical trials [ 22 ]. The authors reported that oral inositol supplementation reduced BMI and that this effect was particularly pronounced in people over 40 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…NC is also linked to metabolic disorders such as CVD and atherosclerosis as well as influenced by changes in insulin levels ( 29 ). A recent meta-analysis reported not only the beneficial effects of INSs on BMI reduction but also a stronger association of MI with BMI reduction compared to other derivatives of INS ( 30 ). Moreover, SBP was significantly reduced in the MI group compared to the placebo group ( p = 0.006), while no significant inter-group difference was observed in DBP ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%